La Interacción Docente y su Incidencia en los Procesos Educativos de losEstudiantes de Educación Básica - Sichi Ojanama, Amparo Isabel (2025)
The aim of our article is on how teacher-student interaction affects motivation, learningand the formation of values-attitudes in basic education, identifying the teachingcompetence that supports these processes; providing evidence to redesign training andpedagogical practice towards more humanizing classrooms; the method used is asystematic literature review 2019-2024, which selected ‘XX’ studies in databases such asScopus, SciELO, Dialnet, Redalyc, EBSCO, GADE, Research Gate and university publishers. The results revealed that the researchers agree that bonds characterized by empathy, articulate communication and continuous feedback enhance intrinsic motivation, promote meaningful learning through scaffolding and cooperation, and strengthen prosocial values and attitudes of self-efficacy, while socioemotional teaching competence emerges as a decisive predictor of classroom climate and performance. To conclude, pedagogical interaction articulates cognitive and affective dimensions, which is why socioemotional skills, flexible planning and formative assessment should be considered in initial and in-service training to ensure inclusive and quality education.